KOMPARASI BEBAN KONSTRUKSI BANGUNAN KONVENSIONAL (SEDERHANA) DAN BANGUNAN NON KONVENSIONAL, STUDI KASUS BANGUNAN SATU LANTAI - Abdullah, Abdullah; Risna, Nevy (Jurnal Teknik Indonesia, 2022)
Many people use new building materials but are guided by old materials, which are actually a lot different. The purpose of this study is to calculate the ratio between dead loads on buildings with conventional (simple) structures and dead loads on buildings with non-conventional structures. This knowledge is important as a basis for calculating building structures. The object of this research is the building model as the basis for calculating the volume of materials. For this model, a simple building design is made with two different structural designs. The first is with a conventional structural design, namely a structure that is commonly used in society, while the second design uses a non-conventional structure, namely a structure that is often used in modern buildings, using the latest materials and construction. Calculation of construction loads using the unit weight of materials obtained from building materials brochures, or also standards that are already available from the literature, and if it is difficult to find standards or brochures, direct measurements are carried out, namely by weighing the materials to be measured. From the calculation results, the total construction weight in simple buildings is 124.299 Kg, while in non-conventional buildings it is 74,392 Kg. The conclusion is that the weight of simple building construction is 1.67 times heavier than the weight of non-conventional building construction.Keywords: comparison, construction, building